Adverse events during nursing care procedure in intensive care unit: The PREVENIR study. (October 2020) - Lesny, M.; Conrad, M.; Latarche, C.; Sylvestre, A.; Gaujard, E.; Dubois, V.; Quignard, C.; Citro, V.; Thomas, J.C.; Bridey, C.; Weber, A.M.; Simon, C.; et al.
Abstract: Objectives: Intensive care unit patients undergo several nursing care procedures (NCP) every day. These procedures involve a risk for adverse events (AE). Yet, their prevalence, intensity, and predisposing risk factors remain poorly established. The main objective of the study was to measure the incidence and severity of NCP related AE. Design: This prospective observational multicentre study was conducted in 9 ICUs. All NCP were recorded for four consecutive weeks. For each NCP, the following were collected: patients' baseline characteristics, type of NCP, characteristics of the NCP, AE and therapeutic responses. Results: 5849 NCP occurred in 340 patients. Among the 340 patients included, 292 (85.9%) were affected by at least one AE, and 141 (41.5%) by an SAE during a NCP. Thirty % of NCP were associated with at least one AE: hemodynamic AE in 17.1%, respiratory AE in 13.6%, agitation and pain (3.7% and 3.3%). Eight invasive devices were accidentally removed. Severe Adverse Events (SAE) occurred in 5.5% of NCP. The main risk factor associated with SAE was pain/agitation at the beginning of the NCP. Conclusion: AE are frequent during NCP in ICU. We identified several risk factors, some of them preventable, that could be considered for the development of recommendations for the nursing care of critically ill patients. Trial Registration: ClinicalTrials.gov NCT02881645.